PAPR and BER reduction in MU-MIMO-OFDM systems via a set of waveforms - Sim, Z.; Reine, R.; Zang, Zhuquan; Gopal, Lenin (2017)
© 2017 IEEE. The challenges faced in the design of multiuser multiple-input multiple-output orthogonal frequency division multiplexing (MU-MIMO-OFDM) systems are the high peak-To-Average power ratio (PAPR) in the transmitted signal and interference occured among the different users. Shaping the subcarriers in a proper way can reduce the PAPR of the OFDM signal effectively and minimize the interference among users. This paper proposes to use computationally efficient optimization method to design a set of waveforms to shape the subcarriers for PAPR reduction and BER improvement in the MU-MIMO-OFDM systems. Numerical results illustrate that the designed set of pulse shaping waveforms is efficient in reducing the PAPR of the transmitted signal while improving the BER in MU-MIMO-OFDM systems.